Arab Republic of Egypt : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
KEY ISSUES The 2014 Article IV consultation takes place when the authorities have started to address longstanding economic challenges. For a number of years Egypt has suffered from low and non-inclusive growth and from high unemployment. Since 2011 these problems have been compounded by large fiscal deficits and rising public debt and by external fragility evidenced by loss of foreign exchange reserves. In 2014, Egypt adopted a new constitution and elected a new president who was candid with the electorate on the need to reform the economy. The government has developed a plan centered on structural reform and investment promotion to raise growth and create jobs, and fiscal adjustment to bring the budget deficit and public debt under control. Crucially, the authorities have already begun to implement fuel subsidy reform, raising prices by 40-80 percent in July 2014. They have also begun the reforms needed to raise tax revenue and to make Egypt a more attractive destination for investment. There was agreement that the authorities' objectives are ambitious but are broadly within reach with steady policy implementation. The authorities aim to raise growth to 6 percent per annum, reduce annual inflation to 7 percent, bring down the fiscal deficit to 8 percent of GDP and debt to 80-85 percent of GDP, and increase foreign exchange reserves to 3 1\2 months of imports, all within the next five years. Staff considers these objectives appropriately ambitious, although targeting a higher level of reserves would be prudent. It believes that the authorities' policies, if followed steadfastly, are broadly consistent with these objectives, but noted that a number of policies-including the details of some fiscal measures and structural measures to improve the business environment-are still being formulated. The authorities and the staff differed somewhat on the extent of vulnerabilities and risks. The authorities are confident that they will be able to follow through on their policies and that improved confidence will lead to a surge in foreign investment, a pickup in tourism, and strong economic growth. Staff emphasized that the authorities' policies would still leave significant vulnerabilities, namely high public debt and large financing gaps, which would need to be covered by greater adjustment or financing, or a combination of the two. Staff also pointed to the difficulty of maintaining tight fiscal and monetary policies over a long period, the risks of dilution of structural reform efforts, and the uncertain regional security environment. To contain these vulnerabilities and risks, staff recommended developing contingency measures in the budget, taking steps to build up reserves buffers, and greater exchange rate flexibility to restore competitiveness. However, staff also agreed that with steadfast commitment to reform, Egypt's prospects could be stronger than assumed in staff's projections. In particular, the recovery in investment could exceed expectations.